Konsep Hadhanah dalam Hukum Islam; Pendekatan Shared Parenting Setelah Perpisahan - Nofan Nurkhafid Azmi; Diana Farid; Muhammad Husni Abdulah Pakarti (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Conflicts of custody of children (hadhanah) after divorce are still an important issue in Islamic family law. The classical fiqh approach that tends to apply split custody is often oriented towards determining the party who has the most right to take care of the child, thus potentially limiting the involvement of one parent in the parenting process. This study aims to analyze the concept of shared parenting (shared custody) as an alternative parenting model in contemporary Islamic family law that is oriented towards the best interests of the child. The research uses normative juridical methods with a statutory and conceptual approach through an analysis of the Compilation of Islamic Law, relevant laws and regulations, as well as contemporary Islamic jurisprudence and family law literature. The results of the study show that the provisions of Article 105 of the Compilation of Islamic Law which prioritize mothers as caregivers of children who have not yet been mumayyiz do not remove the rights or obligations of fathers to continue to actively participate in the maintenance, education, protection, and fulfillment of children's needs. The concept of shared parenting offers a collaborative parenting pattern that allows both parents to continue to carry out responsibilities proportionately even though the marital bond has ended. This model is in line with the principles of Maqāṣid al-Syarī'ah, especially the protection of religion, soul, intellect, and posterity, and strengthens the paradigm of Islamic family law that is more adaptive, just, and oriented towards the welfare of children than the exclusive custody approach.